Conceptual plan for the Turtle Lake irrigation and wildlife area - Weigel, James, author; Schaack, Jerry, author; Jamison, Warren, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
The Turtle Lake Irrigation Area (TLIA) is located in near the town of Turtle Lake in central North Dakota. The TLIA is adjacent to the McClusky Canal, a project feature of the Garrison Diversion Unit (GDU), which transports Missouri River water into the area. The GDU Reformulation Act of 1986 authorized the development of 13,700 acres (5,500 hectares) of irrigation in the TLIA. The conceptual plan presented in this paper is the first step in a process to develop a water delivery project, which places equal emphasis on wildlife, irrigation and economic development in the Turtle Lake area of North Dakota. The planning process and the conceptual plan emphasize sharing of wildlife and agricultural benefits on the same parcels of land, avoidance of environmental impacts, development of wildlife and agriculture enhancement features, and onsite mitigation. The process and concepts are unique relative to normal project-planning efforts and project features. The plan is the result of a cooperative effort by local landowners, with assistance from an interagency planning team, comprised of federal, state and local agencies to envision a multipurpose water development project. The project has not been developed as of 1996; however, planning and implementation efforts are proceeding.
1996 USCID wetlands seminar
Turtle Lake irrigation and wildlife area
Not digitized by CSUL Digital Services.
Presented at Water for agriculture and wildlife and the environment: win-win opportunities: proceedings from the USCID wetlands seminar on June 27-29, 1996 in Bismarck, North Dakota.